PENGARUH EFEKTIVIFITAS PENERAPAN, KESESUAIAN TUGA DAN KEPERCAYAAN SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA KARYAWAN PADA LEMBAGA PERKREDITAN DESA (LPD) PEMAKAI SISTEM DIGITAL DI KECAMATAN PENEBEL - Gusti Ayu Putu Agung Desyani; I Putu Nuratama (UNHI Press, 2021)
This study aims to determine the effect of the effectiveness of the application of accounting information systems, the suitability of accounting information system tasks and the belief in accounting information systems on employee performance at the Village Credit Institutions (LPD) digital system users in Penebel District. This research was conducted at LPDs throughout Penebel District with a population of 28 LPDs with a sample size of 139 respondents. The sampling technique used in the study was purposive sampling. The data analysis method used is multiple linear regression analysis. The results showed that the effectiveness of the accounting information system application had no significant effect on employee performance, the task suitability of the accounting information system had no significant effect on employee performance, and the belief in the accounting information system had a positive and significant effect on employee performance.